Fixing Federal E-Voting Standards. - Barr, Earl; Bishop, Matt; Gondree, Mark (Communications of the ACM, 2007)
The article discusses necessary measures that the United States government must take to fix electronic voting standards. Unless a threat model and a system model is put into place, electronic voting will not be guaranteed to be accurate. The main reasons that electronic voting systems have failed when put into practice are poorly designed systems which do not meet expectations for correctness, availability, accessibility, or security, and a flawed certification process that doesn't express a coherent set of requirements for the systems. Methods to eliminate these problems are presented.